Developing a conceptual framework for staff development in Malaysia nursing home - M. Shafhuan B. Yusran; Hasif Rafidee Hasbollah; Mohd Firdaus Mohd Nasir (Universiti Malaysia Kelantan, 2015)
Nursing staff that had been assigned duties for the residents including provide personal care, assisting with activities and medications, serving meals, and completing resident’s laundry and housekeeping. Sometimes, too many responsibilities by taking care of residents may lead to working extra hours. Due to this, nursing staff will experience frequent changes in their working shifts, resulting into extended overtime and working at days off that may result into turnover. Turnover may lead into potential negative health outcome for nursing home residents in nursing staff payment (salary, wages and other beneficiation) are disproportionate compare to their working hours. It is because of nursing home nurses are the lowest paid employees in healthcare labour force. Understanding turnover in nursing homes are important because it can influence the operation of a nursing home. The purpose of this paper is to identify the characteristics that contribute to the staff turnover by developing a conceptual framework for staff development in retaining the staff in a nursing home. Four characteristics that have been identified which are people, program, process and rewards.